Determinants of Intention to Purchase Energy-Efficient Appliances: Extended Technology Acceptance Model - Elangovan, Anandhi; Babu, Manivannan; Gayathri, J.; Sathya, J.; Indhumathi, G. (International Journal of Energy Economics and Policy, 2024)
Energy is the most important factor for our daily lives, but traditional energy sources like coal, petroleum and gas were polluting the environment. To address this issue, people are considering energy-efficient technologies, which consume less energy and eco-friendly in nature. This paper investigates the factors influencing the intention to purchase of energy-efficient appliances in India. Utilizing the Technology Acceptance Model (TAM), the study examines how perceived ease of use, perceived usefulness, functional value, perceived cost, environmental concern affects their intention to purchase. Non-probability convenience sampling technique was applied. Based on the results, perceived ease of use, perceived usefulness, functional value, perceived cost, environmental concern positively influences the intention to purchase energy-efficient appliances. The eco-friendly purchasing behaviour has significant societal implications, including reduced carbon emissions, conservation of natural resources and environmental sustainability.